Predicting Risk Propensity Through Player Behavior in DOTA 2: A Cross-Sectional Study - Lyu, Sihua; Zhao, Nan; Zhang, Yichuan; Chen, Wenwen; Zhou, Haiyan; Zhu, Tingshao (Frontiers in Psychology, 2022)
As traditional methods such as questionnaires for measuring risk propensity are not applicable in some scenarios, a non-intrusive method that could automatically identify individuals’ risk propensity could be valuable. This study utilized Defense of the Ancients 2 (DOTA 2) single match data and historical statistics to train predictive models to identify risk propensity by machine learning methods. Self-reported risk propensity scores from 218 DOTA 2 players were paired with their behavioral metrics. The best-performing model occurred with Gaussian Process Regression. The root mean squared error of this model was 1.10, the correlation between predicted scores and self-reported questionnaire scores was 0.44, the R-squared was 0.17 and the test-retest reliability was 0.67. We discussed how selected behavioral features could contribute to predicting risk propensity and how the approach could be of potential value in the application of perceiving individuals’ risk propensity in game scenarios and the customization of AI systems in games.